The association of knowledge, attitude and practice with 24 hours urinary sodium excretion among Malay healthcare staff in Malaysia - Diana Mahat,; Zaleha Md Isa,; Azmi Mohd Tamil,; Mohd Ihsani Mahmood,; Fatimah Othman,; Rashidah Ambak, (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Introduction The most effective and affordable public health strategy to prevent hypertension, stroke and renal disease is by reducing daily salt consumption. Therefore, this study aims to determine the association of knowledge, attitude and practice on salt diet intake and to identify foods contributing to high sodium intake. Methods Secondary data analysis was performed on MySalt 2016 data. It was conducted from November 2015 until January 2016 which involving Ministry of Health Staff worked at 16 study sites in Malaysia. Salt intake was measured using 24 hours urinary sodium excretion. Food frequency questionnaire was used to determine the sodium sources. Knowledge, attitude and practice of salt intake were assessed using a validated questionnaire adapted from WHO. Demographic data and anthropometric measures also were collected. Sodium levels of more than 2400mg/day was categorised as high sodium intake. Data were analysed using SPSS software version 21. Results The mean sodium intake estimated by 24 hours urinary sodium excretion was 2853.23 + 1275.8 mg/day. Food groups namely rice/noodles (33.8%), sauces/seasoning (20.6%), meat and poultry (12.6%) and fish/seafoods (9.3%) were the major contributors of dietary sodium. In multiple logistic regression analysis, being a male (aOR=2.83, 95% CI 2.02 – 3.96) and obese (aOR=6.78, 95% CI 1.98 – 23.18) were significantly associated with high urinary sodium excretions. In addition, those who were unsure that high salt intake can cause hypertension (aOR=1.24, 95% CI 0.65 – 2.36), those who think that they consumed too much salt (aOR=2.10, 95% CI 1.13 – 3.87) and those who only use salt rather than other spices for cooking (aOR=2.07, 95% CI 1.29 – 3.30) were significantly associated with high urinary sodium excretion. Conclusions This study showed that the main sources of sodium among Malay healthcare staff is cooked food. Poor knowledge and practice towards reducing salt consumption among them contributes to the high sodium consumption. The practice of healthy eating among them together with continuous awareness campaign is essential in order to educate them to minimize sodium consumption and to practice healthy eating.